The Impact of Intravitreal Avastin on Systemic Blood Pressure in Patients Under Blood Pressure Control - Bilal Khan, Javed Ur Rahman, Nesr Farooq, Ayyaz Hussain Awan, Muhammad Zia Iqbal, Saad Mushtaq Malik, Nazli Gul, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The objective of this study was to examine how intravitreal avastin affected systemic blood pressure in patients with managed hypertension. Methods: Seventy patients with retinal vascular diseases were included in this study. Blood pressure readings were taken from patients before intravenous administration (IVA) to establish a baseline, then again 1 day, 1 week, 4 weeks, and finally monthly for a minimum of 3 months. Avastin was administered intravitreally at a concentration of 0.05 ml to all patients. Data was examined with the help of SPSS 22.0. Results: There were 38 (54.3%) males and 32 (45.7%) females among all cases. Patients mean age was 65.13±8.37 years. On the first day after injection, 92% of patients noticed an increase in blood pressure compared to their baseline. At the 1-week, 4-week, and other time points, there were no statistically significant changes in blood pressure. following injection. Conclusion: Our study found that intravitreal avastin is safe for treating ocular vascular disorders in patients with controlled hypertension. Keywords: systemic blood pressure, avastin, digital sphygmomanometer, ocular pathology.